Ability of fermented soymilk byLactobacillus plantarum 1 in bile acids binding - Yusmarini .; Indrati R.; Utami T.; Marsono Y (Indonesian Journal of Pharmacy, 2010)
Some  lactic  acid  bacteria  (LAB)  strains  have  been  isolated  from spontaneously  fermented  soymilk  which  showing  proteolytic  activity.  These isolated  were  expected  could  producing  bioactive  peptides  that  could  lowering cholesterol content when they used for soymilk fermentation. This research was aimed to  determine  the  proteolytic activity of Lactobacillus  plantarum  1 R.1.3.2 and  L.  plantarum  1 R.11.1.2  comparing  with  L.  acidophilus FNCC  0051  as  acontrol. Furthermore soymilk fermented with these  isolates were monitored for their ability to bind bile acid and these results were compared with the control of soymilk  with  no  fermentation.  Proteolytic  activities  (U/mL)  were  measured spectrophotometrically  using  tyrosin  as  a  standard  product,  while  bile  acid binding   capacity  (µM/100  mg  protein)  using  Total  bile  Acid  Binding  Kit.  The results  show  that  all  isolates  use  in  this  study  had  no  different  proteolytic activity nor bile acid binding capability to that of control strain. The fermentation process could increased their ability to bind with the bile acid.Key words :fermented soymilk, proteolytic lactic acid bacteria, bile acid binding